Multiphase Nanoparticles from Eggshell Waste as Antibacterial Agents Against Rice Blight in Lampung - Rodhiansyah Djayasinga; Wasinton Simanjuntak; Sumardi Sumardi; Sutopo Hadi; Mimi Sugiarti; Hartanti Hartanti; Rudy Tahan Mangapul Situmeang (Pandawa Institute, 2026)
This study reports the first isolation of an Enterobacter cloacae complex (ECC) strain, closely related to Enterobacter hormaechei (99.86% 16S rRNA identity), associated with bacterial blight symptoms in rice in Lampung, Indonesia. Acknowledging 16S rRNA limitations within ECC, species identification is reported cautiously, while pathogenicity profile fulfilled Modified Koch's Postulates. To address chemical bactericide limitations, we developed sustainable multiphase nanoparticles from chicken eggshell waste through mechanical and thermal decomposition approaches. The produced nanoparticles were characterized using XRD, TEM, FTIR, SEM-EDS, PSA, and UV-DRS. The results showed that the nanoparticles consisting of Ca(OH)2, CaO, and β-tricalcium phosphate, with a dimension of 11–31 nm (XRD) and 20–23 nm (TEM). The FT-IR/EDS data confirmed OH⁻, Ca, O, and P elements, while UV-DRS showed a bandgap energy of 5.96 eV. Descriptive statistical analysis (n=6) evaluated antibacterial activity via disk diffusion (20 µg/disk) against the ECC isolate, compared to ampicillin sulbactam (SAM 20). Nanoparticles yielded a mean inhibition zone of 10.06±0.02 mm for responsive replicates, demonstrating moderate activity. Within the zones, bacterial cells showed morphological damage, likely caused by Ca²⁺ and OH⁻ release, inducing membrane disruption and oxidative stress. Furthermore, spatially graded element distribution (Ca, O, P) and β-TCP as a controlled release matrix support sustained bioactivity. These findings reveal eggshell-derived nanoparticles as a promising, economical, and environmentally friendly antibacterial agent for sustainable rice disease management.